Tunable shape recovery progress of thermoplastic polyurethane by solvents. Issue 1 (2nd January 2018) - Wang, Changchun; Kou, Bo; Hang, Zusheng; Zhao, Xuejuan; Lu, Tianxuan; Wu, Ziqi; Zhang, Jin-Peng
Abstract : Purpose: This study aims to present that the chemo-responsive shape recovery of thermoplastic polyurethane (TPU) is tunable by solvents with different solubility parameters, and it is generic for chemo-responsive shape-memory polymer and its composites. Design/methodology/approach: Two kinds of commercial TPU samples with different thicknesses were prepared by panel vulcanizer and injection molding (an industrial manner) to investigate their chemo-responsive shape memory properties in acetic ether and acetone. Findings: Results showed that all of TPU films with different thicknesses can fully recover their original shapes weather they recover in acetic ether or acetone. But the recovery time of TPU films in acetone is greatly reduced, especially for the twisting samples. The residual strains of recovery TPU samples after extension reduce obviously. Research limitations/implications: The great decrement of recovery time is related to two factors. One is due to the bigger solubility parameter of acetone with higher dipole moment compared with those of acetic ether, and the other is the remained internal stress of TPU films after preparation. The internal stress is identified to have an effect on the shape-memory properties by comparing the recovery process of samples with/without annealing. The reduced residual strains of recovery TPU samples after extension is due to the increasing mobility of polymer segments after molecules of acetic ether penetrates into the polymeric chains. Originality/value: This is a universal strategy to control the recovery process of shape-memory materials or composites. The underlying mechanism is generic and should be applicable to chemo-responsive shape-memory polymers or their composites.